PENGEMBANGAN INSTRUMEN PENILAIAN KERJA PRAKTIKUM BIOLOGI PADA MATERI SISTEM EKSKRESI KELAS VIII DI SMPN 6 PALOPO - Ansar, Fitriani; khaerati; Muhajirah Yunus, Nur; Dwi Aristy Putri, Iin; Nurasia (Jurnal Biogenerasi, 2024)
This research aims to determine the the process of developing thevalidity, practicality, and rehability of the biology practicum assessment instrument in the System Exrection. This research is a type of Research and Development (RnD) study with a research design using four step models. Data collection techniques used are observation, interviews, and questionnaire surveys. The sample involved a total of 31 students. The development technique and validation of the biology practicum assessment instrument in the System Exrection for grade VIII wee carried out using a simple random sampling method. The research results show that: (1) in SMPN 6 Palopo, the validator I obtained 86,6% and validator II obtained 83,3% with very criteria; (2) the practicality analysis of the development of the biology praacticum assessment instrumen in the System Exrection based on the response from teacher obtained 84% and the response from students obtained 88% with very practical criteria; (3) the educational effectiveness analysis of the System Exrection for grade VIII at SMPN 6 Palopo obtained 93% with very effective and feasible criteria for use. Based on the research results, the assesment instrument for the biology practicum is considered valid for use.